LEADERSHIP AND SOCIAL CAPITAL IN HANDLING FOREST AND LAND FIRES IN MUARO JAMBI REGENCY - Wahid, Makmun; Baidawi, Ahmad (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
Dealing with forest and land fires is not an easy matter, but a complex one. Handling forest and land fires requires the role of a leader in providing solutions to existing problems. There have been many efforts by local governments to stop forest and land fires, but have yet to achieve significant results. The development of land use into oil palm plantations is the dominant reason for forest and land fires occurring in various regions. Especially for areas that have peat ecosystems such as Muaro Jambi Regency which has made the main potential for forest and land fires in the area higher. This study aims to see how the role and strategy of the local government of Muara Jambi Regency in dealing with forest and land fires in Muaro Jambi Regency and the form of leadership from the regional head of the Muaro Jambi Regency in coordinating the parties involved in the process of handling forest and land fires in the Muara Jambi Regency. The method used in this research is descriptive qualitative research. From the results of the analysis, we can conclude that leadership and management of social capital must be able to synergize to be able to deal with forest and land fires in Muaro Jambi Regency this means that the process of handling forest and land fires in Muaro Jambi Regency cannot be done by the government alone, but requires a collaboration between the government and the community and handling in physical matters is not enough, it takes a trust, cooperation and a strong network (network) to get maximum results.